OP0142 Methotrexate Use in RA: What 17 Years and 22, 621 Patients Can Teach Us. (15th July 2016) - Michaud, K.; Pedro, S.
Abstract : Background: Methotrexate (MTX) remains the gold standard treatment for rheumatoid arthritis (RA), yet most recent research refers to it only as a referent or placebo without context of dose or form of administration. Objectives: To examine the real-world use trends of MTX in the US since 1998. Methods: Using a large observational cohort, the National Data Bank for Rheumatic Diseases (NDB), we characterized patients with RA who initiated MTX from 1998 through 2015. Baseline characteristics were assessed by MTX administration route, injectable (INJ) and oral (PO), and by mono- vs. concomitant DMARD therapy. Discontinuation, described using Kaplan-Meier survival curves, was defined as either ending MTX or adding another DMARD. Sensitivity analyses were performed with alternative discontinuation definitions. GEE were also used to model change on MTX dose over time. Results: In our study of 22, 621 RA patients, MTX had widespread use with 73.5% ever being exposed, 59.4% using it during our study, and 11.4% initiating without any prior DMARD. The MTX-exposed baseline mean age was 59±13 years, 79% female, and 14±12 years RA duration. Of these, 21% used MTX-INJ and had worse disease severity and higher weekly doses compared to MTX-PO (PAS: INJ 4.1±2.2 vs. PO 3.6±2.2; Dose: INJ 16.2±4.2 vs. PO 13.8±5.5 mg). When initiating MTX, 42.8% took mono-therapy, and concomitant use was split 53/47% on synthetic/biologic DMARDs with trends of being younger, more employed, and more private insurance (34% vs 27% on mono-therapy). Overall median (IQR) survival time after initiating MTX was 2.5 (1–6) years per patient with 24, 823 p-yr followup. Sensitivity analysis of discontinuation requiring ending MTX had 8 (2.5-.) years per patient, 38, 290 p-yr followup. By route, the median (IQR) survival was 1.5 (0.5–3.5) years for INJ and 2 (1–5.5) years for PO with 16.2% of patients switching between routes. Also, survival was 6 (1.5–…) years for mono-therapy and 3 (1–9) years for concomitant therapy. MTX doses increased by 0.01 (95% CI 0.01 – 0.02) mg/yr/patient with 50% of patients increasing MTX dose a median (IQR) of 5 (2.5–10) mg and 3.3% of patients decreasing their dose. Conclusions: Patients who tolerate MTX early tend to use it for several years even while adding concomitant DMARDs. We showed notable differences between patients by MTX route, with trends of increasing dose over time. Acknowledgement: This study was funded by Pfizer Corp. Disclosure of Interest: None declared